State and Federal Policies for School Facility Construction: A Comparison of Michigan and Ohio. (February 2015) - Davis, Thomas E.
Background: The Ohio School Facilities Commission was set up in response to litigation compelling the state to achieve a more equitable distribution in the quality of school facilities. The American Recovery and Reinvestment Act (ARRA) was a federal policy to stimulate the United States economy and support school facility construction. These two programs provide an opportunity to compare a state-run program to a federal one.Purpose: This study analyzes the distribution of school and community resources across school districts in Michigan and Ohio, two otherwise similar states with very different policies to support school facilities. Using the year prior to the implementation of the ARRA as a baseline, this study then compares the allocation of Qualified School Construction Bonds (QSCB) provided under the ARRA.Research Design: Using Michigan as a control group because of the weak state support for school construction, the analysis shows the distribution and variation of school building capital, community resources, educational inputs, and student outcomes across districts in both states. Based on these indicators, districts that received QSCBs are compared with districts that did not.Findings: Ohio does appear to have a more equitable distribution of capital facilities but the QSCB allocations in Ohio do not appear to be noticeably more equalizing than those in Michigan. Moreover, the allocations in both states went, on average, to districts above the mean on a number of measures of community resources, educational inputs, and student outcomes.